Pengaruh Iklan, Kepercayaan, dan Diskon terhadap Keputusan Pembelian pada Pengguna Aplikasi Shopee: (Survei pada Mahasiswa FEB Universitas Slamet Riyadi Surakarta) - Muhammad Adnan Muizzamith; Sumaryanto, Sumaryanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of advertising, trust, and discounts on purchasing decisions among Shopee app users, focusing on students from the Faculty of Economics and Business, Slamet Riyadi University, Surakarta as respondents. The background of this study departs from the increasing competition in e-commerce in Indonesia, which requires each platform to develop appropriate marketing strategies to attract consumers' attention and build their loyalty. The research method used was a quantitative survey involving 100 respondents selected through a convenience sampling technique, allowing researchers to quickly obtain data from relevant target groups. The collected data were then analyzed using multiple linear regression methods to test the proposed hypotheses. The results showed that consumer trust in the Shopee app has a significant influence on purchasing decisions, meaning that the higher the level of trust, the more likely consumers are to make purchases through the app. In addition, the discount factor was also proven to have a significant influence on purchasing decisions, indicating that price cuts are still an effective strategy in influencing consumer behavior, especially students. Conversely, the advertising variable did not show a significant influence on purchasing decisions, which could mean that the intensity or quality of advertising is not strong enough to drive purchasing decisions in this respondent segment. The findings of this study provide practical contributions for Shopee in designing more targeted marketing strategies, emphasizing the importance of building and maintaining consumer trust, as well as utilizing proven effective promotional strategies such as discounts. Therefore, this study not only enriches the literature on consumer behavior in the e-commerce context but also offers useful recommendations for digital business practitioners in increasing competitiveness.